Gaining resolution when creating imagery of aging - Sheahan, Jacob (Frontiers in Sociology, 2022)
In seeking to support healthy ageing, designers have struggled to reduce their assumptions and biases towards older adults, been seen to interpret the worlds of later life through unfiltered imagery, as well as engage with stigmas, ultimately diminishing the technologies they construct. This article seeks to critically analyse this state-of-the-art from a design research perspective while engaging with the growing interdisciplinary study of ageing and technologies. Towards this, we proposition ‘resolution’ as a concept indicative of the level of detail that seeks to characterise the fidelity that representations of later life have. This concept is explored through a cultural probe study that investigated the sentiments of several older Australians regarding the inequities and social isolation brought on by the COVID-19 pandemic. Providing a diary alongside photovoice and mapping tasks, the study captured perceptions of social technology, practices, networks, and wellbeing, offering a diverse and complex picture of ageing and technology. Through reflexive thematic analyses of some of these materials, this case study offers designers pathways to understanding and including older adults in their work. In determining the resolution of these images of ageing, we discuss how transparency about the limitations and qualities of such participatory methods through incorporating reflexivity can influence the degree of detail such imagery gains. Ultimately this concept builds on the notion of participation configuration, supporting designers to realise better images of ageing and representations of later life.